Ceramic lithium ion conductor to solve the anode coking problem of practical solid oxide fuel cells - Wang, W.; Wang, F.; Chen, Y.; Qu, J.; Tadé, M.; Shao, Zongping (Wiley-VCH Verlag, 2015)
For practical solid oxide fuel cells (SOFCs) operated on hydrocarbon fuels, the facile coke formation over Ni-based anodes has become a key factor that limits their widespread application. Modification of the anodes with basic elements may effectively improve their coking resistance in the short term; however, the easy loss of basic elements by thermal evaporation at high temperatures is a new emerging problem. Herein, we propose a new design to develop coking-resistant and stable SOFCs using Li+-conducting Li0.33La0.56TiO3 (LLTO) as an anode component. In the Ni/LLTO composite, any loss of surface lithium can be efficiently compensated by lithium diffused from the LLTO bulk under operation. Therefore, the SOFC with the Ni/LLTO anode catalyst layer yields excellent power outputs and operational stability. Our results suggest that the simple adoption of a Li+ conductor as a modifier for Ni-based anodes is a practical and easy way to solve the coking problem of SOFCs that operate on hydrocarbons.